Between Law and the Nation State: Novel Representations of the Refugee - Behrman, Simon (Refuge: Canada’s Journal on Refugees, 2021)
Given the degraded profile of the refugee in contemporary discourse, it is tempting to seek alternatives from a rich tradition of literary tropes of exile. However, this article argues that the romanticized figure of the literary exile ends up denying, albeit in positive terms, a genuine refugee voice, as much as the current impersonal hegemonic concept of the refugee as found in law. Ultimately, the spell in which refugees find themselves trapped today can be broken only by opening up a space of politics in which the refugee herself can be heard.